Pharmacodynamics, pharmacokinetics and safety of GSK2190915, a novel oral anti‐inflammatory 5‐lipoxygenase‐activating protein inhibitor. (5th February 2013) - Bain, Gretchen; King, Christopher D.; Schaab, Kevin; Rewolinski, Melissa; Norris, Virginia; Ambery, Claire; Bentley, Jane; Yamada, Masanori; Santini, Angelina M.; van de Wetering de Rooij, Jeroen; Stock, Nicholas; Zunic, Jasmine; et al.
Abstract : Aim: To assess the pharmacokinetics, pharmacodynamics, safety and tolerability of the 5‐lipoxygenase‐activating protein inhibitor, GSK2190915, after oral dosing in two independent phase I studies, one in Western European and one in Japanese subjects, utilizing different formulations. Method: Western European subjects received single (50–1000 mg) or multiple (10–450 mg) oral doses of GSK2190915 or placebo in a dose‐escalating manner. Japanese subjects received three of four GSK2190915 doses (10–200 mg) plus placebo once in a four period crossover design. Blood samples were collected for GSK2190915 concentrations and blood and urine were collected to measure leukotriene B4 and leukotriene E4, respectively, as pharmacodynamic markers of drug activity. Results: There was no clear difference in adverse events between placebo and active drug‐treated subjects in either study. Maximum plasma concentrations of GSK2190915 and area under the curve increased in a dose‐related manner and mean half‐life values ranged from 16–34 h. Dose‐dependent inhibition of blood leukotriene B4 production was observed and near complete inhibition of urinary leukotriene E4 excretion was shown at all doses except the lowest dose. The E C 50 values for inhibition of LTB4 were 85 nm and 89 nm in the Western European and Japanese studies, respectively. Conclusion: GSK2190915 is well‐tolerated with pharmacokinetics and pharmacodynamics in Western European and Japanese subjects that support once daily dosing for 24 h inhibition of leukotrienes. Doses of ≥50 mg show near complete inhibition of urinary leukotriene E4 at 24 h post‐dose, whereas doses of ≥150 mg are required for 24 h inhibition of blood LTB4 .